2021
DOI: 10.1002/aws2.1262
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal assessment of point‐of‐use carbon filters for removal of per‐ and polyfluoroalkyl substances from private well water

Abstract: Eighteen private well users in North Carolina were recruited to test the performance of under-sink, activated carbon block water filters to remove per-and polyfluoroalkyl substances (PFAS). Monthly sampling was conducted for 8 months. Filters were certified for removal of perfluorooctanoic acid and perfluorooctanesulfonic acid under NSF International certification P473, but not for additional short-chain perfluoroalkyl acids or perfluoroalkyl ether acids (PFEAs) evaluated in this study. Out of 47 targeted anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 58 publications
(89 reference statements)
0
2
0
Order By: Relevance
“…A total of 17 PFAS were found in filter influent samples out of 47 targeted analytes ( PFAS 4.7-131 ng/L). Overall, results showed that the filters effectively removed PFAS (97%-99%) in all influents, including short-chain PFEAs, for the total producerrecommended lifetime of the filters (Mulhern et al, 2021).…”
Section: Graphical Abstract 1 Introductionmentioning
confidence: 92%
“…A total of 17 PFAS were found in filter influent samples out of 47 targeted analytes ( PFAS 4.7-131 ng/L). Overall, results showed that the filters effectively removed PFAS (97%-99%) in all influents, including short-chain PFEAs, for the total producerrecommended lifetime of the filters (Mulhern et al, 2021).…”
Section: Graphical Abstract 1 Introductionmentioning
confidence: 92%
“…Also at the home system scale, Mulhern et al (2021) show that in a study of 18 private wells in North Carolina, a commercially‐available point of use (POU) carbon‐block filter certified under NSF's P‐473 protocol for PFOA and PFOS was successful in removing 17 PFAS detected in the filter influent, including short‐chain perfluoroalkyl ether acids (PFEAs). The eight‐month study covered the manufacturer's recommended lifetime for the device.…”
Section: Treatmentmentioning
confidence: 99%
“…Samples were received at RTI on 1 April 2021 and analyzed for a panel of 20 metals (Table S1) and 25 PFAS (Table S2) according to methods approved by the U.S. Environmental Protection Agency (EPA). The fully specified conditions for both methods have been described in detail previously [36,37].…”
Section: Sampling and Analysismentioning
confidence: 99%